Effects of Pursed Lip Breathing on Dynamic Hyperinflation after Glittre ADL Test in Chronic Obstructive Pulmonary Disease Patients - Santiworakul, Anoma; Saithonginn, Priyanuch; Binlateah, Aswanee; Samkaew, Jarturon; Dorkor, Suraiyah; Isahoh, Nifaridah; คงขำ, อัครเดช (NU Journal of Nursing and Health Sciences, 2019)
This research was study the effects of pursed lips breathing during performance of the Glittre activities of daily living (Glittre-ADL) test on dynamic hyperinflation, oxygen saturation, and ADL performance in COPD patients. Method: Ten Chronic obstructive pulmonary disease (COPD) patients, aged older than 60 years, in moderate to severe stages were included in the study. A randomized crossover study design was used, dividing patients into pursed lips and nonpursed lips groups during performance of the Glittre-ADLtest. Inspiratory capacity, which determines dynamic hyperinflation and oxygen saturation, was measured before and after the Glittre-ADLtest for all participants. Time spent on the Glittre-ADLtest, which determines ADL performance, was also measured.Result: The group that performed pursed lips breathing during the Glittre-ADLtest showed significantly lower dynamic hyperinflation and higher oxygen saturation scores than the other group (p-value < 0.05). However, there was no significant difference in the time spent on the Glittre-ADLtest between the two groups.